Enhanced Photocatalytic and Filtration Properties of Carbon-Doped g-C3N4 Membranes Reinforced with Nanofibrillated Cellulose - Beiyue Xiong; Yirong Liu; Wenbiao Zheng; Xiaoxiao He; Chengning Ye; Hanyu Xue; Jianrong Xia; Renjin Gao; Liwei Wang (BioResources)
Carbon-doped g-C3N4 was synthesized using a simple high-temperature process (calcination at 550 °C for 4 h). One-dimensional nanofibrillated cellulose (NFC) materials were then inserted into the two-dimensional g-C3N4 material by vacuum filtration method at room temperature. The prepared g-C3N4/NFC composite membranes were systematically characterized using a series of techniques, such as XRD, FTIR, and SEM. The results showed that the carbon-doped photocatalysts possessed a narrow band gap, which prolonged the visible light absorption and favored the organic pollutant degradation. The incorporation of NFC enlarged the interlayer spacing, leading to an increase in the water flux. The water flux of C0.02CN/NFC (15%) composite membranes reached 73.7 L•m-2•h-1•bar-1, which is more than that of g-C3N4/NFC membrane. At the same time, the carbon doped composite membranes showed enhanced retention and photocatalytic degradation ability. The retention rate of the C0.02CN/NFC (5%) composite membranes could reach 89.3% from 80.8% after three-cycle photocatalytic experiments. The membrane maintained a good retention rate and feed flux, which confirms the composite membrane has good self-cleaning ability and stability. It could potentially be applied for water treatment.